Simulated decadal oscillations of the Atlantic meridional overturning circulation in a cold climate state - Yoshimori, Masakazu; Raible, Christoph; Stocker, Thomas; Renold, Manuel (2018)
The significance of the Atlantic meridional overturning circulation (MOC) for regional and hemispheric climate change requires a complete understanding using fully coupled climate models. Here we present a persistent, decadal oscillation in a coupled atmosphere-ocean general circulation model. While the present study is limited by the lack of comparisons with paleo-proxy records, the purpose is to reveal a new theoretically interesting solution found in the fully-coupled climate model. The model exhibits two multi-century-long stable states with one dominated by decadal MOC oscillations. The oscillations involve an interaction between anomalous advective transport of salt and surface density in the North Atlantic subpolar gyre. Their time scale is fundamentally determined by the advection. In addition, there is a link between the MOC oscillations and North Atlantic Oscillation (NAO)-like sea level pressure anomalies. The analysis suggests an interaction between the NAO and an anomalous subpolar gyre circulation in which sea ice near and south of the Labrador Sea plays an important role in generating a large local thermal anomaly and a meridional temperature gradient. The latter induces a positive feedback via synoptic eddy activity in the atmosphere. In addition, the oscillation only appears when the Nordic Sea is completely covered by sea ice in winter, and deep convection is active only near the Irminger Sea. Such conditions are provided by a substantially colder North Atlantic climate than today